2019
DOI: 10.1007/s00405-019-05627-x
|View full text |Cite
|
Sign up to set email alerts
|

Anterolateral thigh free flap in reconstruction of lateral skull base defects after oncological resection

Abstract: PurposeEvaluation of the utility of the free anterolateral thigh flap reconstruction of the defects resulting from radical temporal bone resection in the management of lateral skull base malignancies in a single institution.MethodsAn analysis of 17 en bloc subtotal petrosectomies for removal of malignant tumours was performed. There were 12 squamous cell carcinomas, 4 basal cell carcinomas and 1 adenoid cystic carcinoma. The tumours were staged with the University of Pittsburgh TNM system. In all patients, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
(49 reference statements)
1
13
0
Order By: Relevance
“…Many publications have reported postoperative complications of free ap for skull base reconstruction and its risk factors. The overall complication rate of a variety of the free aps is 10-32%, and partial or complete ap failure occurs in 2-9% [3,25,26,12,7,27]. The overall incidence of complications in this series was 17.6% and the rate of ap loss was 5.9%, which compared well with the literature.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Many publications have reported postoperative complications of free ap for skull base reconstruction and its risk factors. The overall complication rate of a variety of the free aps is 10-32%, and partial or complete ap failure occurs in 2-9% [3,25,26,12,7,27]. The overall incidence of complications in this series was 17.6% and the rate of ap loss was 5.9%, which compared well with the literature.…”
Section: Discussionsupporting
confidence: 80%
“…In the present series, the ALT ap was used in all but 2 of the cases to reconstruct composite skull base defects. The ALT ap has been described more frequently in the last decades' publications [3]. The ALT ap, based on the descending branch of the lateral circum ex femoral artery, has many advantages of RAM ap such as reliability, long vascular pedicles, versatility in the components and two team approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been reported that the failure rate of free flap repair is 2–9% ( 38 ). Advanced age and cardiovascular disease proved to increase the risk of flap ischemia ( 38 ). In the group, there is a patient with high risk of thrombosis who developed both necrosis of the flap and cerebral infarction after operation.…”
Section: Discussionmentioning
confidence: 99%
“…The flap can be harvested without changing intraoperative positioning, which allows both the recipient-site team and the donor-site team to operate simultaneously. Some studies have confirmed the effectiveness of the anterolateral thigh flap in repairing large skull base defects (29,38). However, it has been reported that the failure rate of free flap repair is 2-9% (38).…”
Section: Reconstruction Of the Skull Basementioning
confidence: 99%